Dolutegravir Cerebrospinal Fluid Diffusion in HIV-1–Infected Patients with Central Nervous System Impairment - Gelé, Thibaut (Open Forum Infect Dis, 2019)
This study aimed to determine dolutegravir cerebrospinal fluid (CSF) diffusion in 13 patients with HIV-related cerebral impairment enrolled in a real-life observational study. Dolutegravir median (range) CSF concentration [9.6 (3.6–22.8) ng/mL] reached CSF therapeutic concentrations whatever the blood-brain barrier status and diffused in correlation with the albumin quotient (P = .0186).